Simulations of stratospheric sudden warmings in the Berlin troposphere-stratosphere-mesosphere GCM - Erlebach, P.; Langematz, U.; Pawson, S. (Annales Geophysicae, 1996)
Stratospheric sudden warming events in the Northern Hemisphere of the Berlin TSM GCM are investigated. In about 50% of the simulated years (13 out of 28), major midwinter warmings occur. This agrees well with observations but, whereas real events tend to occur approximately every second season, those in the model are clustered, most of them occur in the period between years 15/16 and years 24/25. In most other years, minor warming events take place. The warming events are found earlier in the winter than in reality. Many of the observed characteristics of warming events are well captured by the model: pulses of wave activity propagate out of the troposphere; these transient events force the zonal-mean zonal wind in the stratosphere and coincide with increases of the temperature at the North Pole and cooling at low levels in the tropics; temperature changes of opposite sign are modelled at higher levels. Synoptically, the modelled stratosphere evolves quite realistically before the warmings: the cyclonic vortex is displaced from the Pole by an amplifying anticyclone. After minor warmings, the stratosphere remains too disturbed as the cyclonic centre does not return to the North Pole as quickly as in reality. In the aftermath of major warmings the cyclonic vortex is not fully eroded and the anticyclonic circulation does not develop properly over the Pole; furthermore, the wintertime circulation is not properly restored after the event.